ANALYSIS OF SODIUM (Na) CONTENT IN PORANG (AMORPHOPHALLUS ONCOPHYLLUS) PLANT - Rachmat, Rachmat Sahputra (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2024)
The nutritional content contained in the porang plant, as is the case with other root crops, also contains carbohydrates, contains fat, protein, minerals, vitamins and fiber. This study aims to obtain data on the average sodium mineral content in Porang plants. The analytical method uses an atomic absorption spectrometer (AAS) in flame emission mode. Sample solutions containing sodium were stored in polyethylene bottles. Sodium has a maximum light emission at a wavelength of 589 nm, where the working procedure is that the sample is nebulized into a gas flame to allow controlled excitation to occur. The sodium resonance spectral line at 589 nm is isolated with an interference filter or with a light dispersing device such as a prism or grating. The intensity of the emitted light is measured with a photomultiplier, or photodiode. The intensity of light at 589 nm will be roughly proportional to the concentration of sodium. From the results of the analysis using the AAS method, it was found that the sodium content in the porang tuber sample was obtained from Nganjuk district, East Java, with a sodium content of 51.25 mg per 1 kg of porang tuber flour or 5.125 mg sodium per 100 g of porang tuber. This content is lower than the sodium content in corn, but higher than the sodium content in rice.